Recency negativity: Newer food crops are evaluated less favorably - Inbar, Yoel; Phelps, Jordan; Rozin, Paul (Appetite, 2020)
Food crops produced by new technologies such as genetic engineering are widely opposed (Gaskell, Bauer, Durant, & Allum, 1999; Scott, Inbar, Wirz, Brossard, & Rozin, 2018). Here, we examine one reason for this opposition: recency. More recently-developed crops are evaluated less favorably, whether they are produced by artificial selection (i.e., conventional breeding), natural or man-made irradiation, or genetic engineering. Negative effects of recency persist in a within-subjects design where people are able to explicitly compare crops developed at different times, and an internal meta-analysis shows that the negative effect of recency is robust across measures and stimuli. These results have implications for the evaluation of crops produced using new modification techniques, including the widespread opposition to genetic engineering.